Pengembangan Real-time Monitoring and Managing Information System Untuk Digitalisasi Data Koleksi Tumbuhan Di Kebun Raya Indonesia - Heri Apriyanto; Wahyu Setyo Prabowo; Rachmawan Adi Laksono; Andarta Fardhanul Khoir; Bayu Adjie; Uus Khusni; Sjaeful Afandi (Labkat Press KA FTIK UNIKOM, 2022)
In the last 2021, Indonesia has had 43 botanical gardens with more than 104.000 specimens that are collected in the Indonesian Botanical Garden. 152 species of them are in threatened condition based on The International Union for Conservation of Nature’s Red List of Threatened Species (IUCN) data. To conserve the floras and exploring them for other purposes such as science development, economic development, and medicine development, the stakeholders including the Indonesian government find it difficult to access the real-time data and information. Indonesia does not have a connected system at the national level that can provide real-time data from all botanical gardens in Indonesia for monitoring and managing the specimens. Some botanical gardens have tried to develop their system to maintain and monitor plant collections. However, without a national connected system that is implemented in all Indonesian gardens, it raises new issues such as long-time collecting data process, inaccurate data, different mechanisms to treat data and different business processes to maintain the plant collections. The purpose of this study is to develop a system, named Makoyana, that can address the issues and provide real-time monitoring and managing information for plant collection at the national level. Software Development Life Cycle (SDLC) and Software Testing Life Cycle (STLC) methodologies are combined to manage the project. The outcomes of this study are the system that provides one gateway platform for stakeholders to find all information about plant collections data, IUCN status, updated statistics, and a national standard for maintaining and collecting data for plant collections in the Indonesian Botanical Garden.